(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the role of tax incentives in ensuring economic stability and issues of increasing their effectiveness. In particular, the current state of tax incentives currently used in Uzbekistan, their impact on economic growth, and problems in the system are studied. Also, based on the experience of foreign countries, proposals and recommendations have been developed to optimize tax incentives and increase their effectiveness. The results of the study serve to improve tax policy and strengthen economic stability.